Developing a framework for flexibility within organisations - C. Koornhof (South African Journal of Business Management, 2001)
Recent research in Management Sciences has shown that flexibility is an essential characteristic of successful enterprises in a highly competitive and rapidly changing business environment (Kogut, 1985; Ansoff, 1988; Pasmore, 1994; Volberda, 1998). Consequently, management should not only understand flexibility but also be able to create flexible organisations and to measure and monitor flexibility. However, flexibility is a nebulous, elusive and multidimensional concept which is poorly understood and seldom managed and measured in enterprises (Gerwin, 1993; Parthasarthy Sethi, 1993; Upton, 1994).The purpose of this article is firstly, to define the construct flexibility and secondly, to develop a conceptual framework that explains its multiple attributes in organisations. This framework is used as a basis for the measurement of flexibility. The article suggests procedures that managers can apply to develop indicators of flexibility and these indicators are used in turn, to identify current levels of flexibility, to set targets for flexibility and to monitor the progress made towards the achievement of these targets.
Keywords: 650